The Causal Component in the Intergenerational Transmission of Income - Monique De Haan; Magnus Stubhaug (CESifo GmbH, 2024)
We apply a partial identification analysis using comprehensive Norwegian register data to investigate the causal effect of father's income on child income. We find a strong association between the incomes of fathers and children. The causal effect, however, equals at least 1% and at most 51% of this observed association. Additionally, we find substantial differences in the intergenerational association and bounds around the causal effect between sons and daughters when considering individual incomes. When examining joint income with their partners, the results are more aligned, indicating that assortative mating plays a key role in intergenerational income transmission, particularly for daughters.
Keywords: J62; C14; D31; 330; intergenerational income transmission; partial identification; intergenerational mobility; nonparametric bounds